iPLEDGE Must Abstain from Abstinence - Lowery, Kami (J Clin Aesthet Dermatol, 2020)
Isotretinoin has unmatched efficacy in the treatment of acne. However, because isotretinoin is a teratogen that can cause profound birth defects, the iPLEDGE program regulates the drug’s distribution in the United States. To minimize fetal exposure to isotretinoin, the program requires that female patients capable of becoming pregnant use two forms of contraception or commit to abstinence while using this therapy. This manuscript argues that iPLEDGE should be revised to remove abstinence as an acceptable contraceptive option in the face of evidence that disputes its efficacy. All patients, regardless of reported sexual activity, should be required to use data-proven contraception. Potential benefits of the proposed change (iPLEDGE-R) include reducing the number of isotretinoin pregnancies, increasing patient privacy protection, and standardizing patient care. Further investigation needs to guide additional strategies to achieve the program’s public health goal; however, the ethical and pragmatic advantages of iPLEDGE-R merit consideration.